Magnetoencephalography Hyperscanning Evidence of Differing Cognitive Strategies Due to Social Role During Auditory Communication - Yoneta, Nano; Watanabe, Hayato; Shimojo, Atsushi; Takano, Kazuyoshi; Saito, Takuya; Yagyu, Kazuyori; Shiraishi, Hideaki; Yokosawa, Koichi; Boasen, Jared (Frontiers in Neuroscience, 2022)
Auditory communication is an essential form of human social interaction. However, the intra-brain cortical-oscillatory drivers of auditory communication exchange remain relatively unexplored. We used improvisational music performance to simulate and capture the creativity and turn-taking dynamics of natural auditory communication. Using MEG hyperscanning in musicians, we targeted brain activity during periods of music communication imagery, and separately analyzed theta (5-7 Hz), alpha (8-13 Hz) and beta (15-29 Hz) source-level activity using a within-subjects, two-factor approach which considered the assigned social role of the subject (Leader or Follower) and whether communication responses were improvisational (yes or no). Theta activity related to improvisational communication and social role significantly interacted in the left isthmus cingulate cortex. Social role was furthermore differentiated by pronounced occipital alpha and beta amplitude increases suggestive of working memory retention engagement in Followers but not Leaders. The results offer compelling evidence for both musical and social neuroscience that the cognitive strategies, and correspondingly the memory and attention-associated oscillatory brain activities of interlocutors during communication differs according to their social role/hierarchy, thereby indicating that social role/hierarchy needs to be controlled for in social neuroscience research.